2013
DOI: 10.1063/1.4825146
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz instability for flow in porous media under the influence of oblique magnetic fields: A viscous potential flow analysis

Abstract: In this paper, the Kelvin-Helmholtz instability of viscous incompressible magnetic fluid fully saturated porous media is achieved through the viscous potential theory. The flow is considered to be through semi-permeable boundaries above and below the fluids through which the fluid may either be blown in or sucked out, in a direction normal to the main streaming direction of the fluid flow. An oblique magnetic field, mass, heat transfer, and surface tension are present across the interface. Through the linear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To minimize the mathematical manipulations, he considered the symmetric and antisymmetric disturbances. Furthermore, Moatimid et al investigated the influences of suction and injection at the boundaries of two‐phase fluids. Moreover, they studied the influence of the normal streaming velocity on the interface instability.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the mathematical manipulations, he considered the symmetric and antisymmetric disturbances. Furthermore, Moatimid et al investigated the influences of suction and injection at the boundaries of two‐phase fluids. Moreover, they studied the influence of the normal streaming velocity on the interface instability.…”
Section: Introductionmentioning
confidence: 99%
“…9,29 At the boundary between the two the Oldroydian viscoelastic nanofluids, the stresses must be balanced. Two types of boundary conditions suffice the properly constrain the field equations: conditions at an infinite (perpendicular) distance from the system and conditions at the dividing interface.…”
Section: Problem Definition and Mathematical Formulationmentioning
confidence: 99%
“…8 He used the multiple time scales method in order to obtain two parametrically a) E-mail: gal_moa@hotmail.com b) E-mail: dr_elham_alali@hotmail.com c) E-mail: hoda_ali_1@hotmail.com nonlinear Schrôdinger equations to describe the elevation of weakly nonlinear capillary waves. As a recent work, in this topic, Moatimid et al 9 discussed the KHI for flow in porous media under the influence of an oblique magnetic field.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The combined study of magnetic field and porous medium on Kelvin-Helmholtz instability in plane geometry in the presence of heat and mass transfer was considered by Awasthi et al 15 Moatimid et al 16 considered the effect of oblique magnetic field on the Kelvin-Helmholtz instability in plane geometry in the presence of heat and mass transfer. Moatimid and Hassan 17 studied the effect of tangential electric field on the Kelvin-Helmholtz instability in cylindrical flow with permeable boundaries including heat and mass transfer in porous media and found that tangential electric field has stabilizing effect.…”
Section: Introductionmentioning
confidence: 99%